The meta-Phillips Curve: modelling U.S. inflation in the presence of regime change - Aristidou, Chrystalleni (Elsevier, 2018)
A novel approach to modelling inflation dynamics is presented based on a set of Hybrid New-Keynesian Phillips Curves, distinguished by the regime duration and measures of real marginal cost, and combined into a meta-Phillips Curve using model averaging techniques. The analysis of US data over 1950q1 - 2016q1 shows that, while the importance of expectations of future inflation varies through time depending on the monetary policy regime and economic environment, future expectations make a more substantial contribution to current inflation than past inflation, and that the labour share is superior to the output gap as a measure of cyclical pressures on prices.